2000
DOI: 10.1038/sj.jhh.1000945
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced exacerbation of morning surge in blood pressure in patients with essential hypertension

Abstract: The morning surge in blood pressure (BP) is related to the morning occurrence of lethal cardiovascular events. We tested the hypothesis that salt intake may be associated with the morning surge in BP in essential hypertension. Seventy-six patients were admitted and placed on a low salt diet (2 g/day) for 7 days followed by a high salt diet (20-23 g/day) for another 7 days. At the end of each salt diet, 24-h ambulatory BP and heart rate monitorings and head-up tilt (HUT) test were performed. Patients whose aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
0
32
0
2
Order By: Relevance
“…2 We further showed that salt-sensitive hypertension manifests an absent or decreased nocturnal reduction in blood pressure, 30 and nondippers, ie, patients with an absent or decreased nocturnal reduction in their blood pressure, tend to have more severe target-organ damage than do dippers, ie, those with a normal nocturnal decrease in blood pressure. 31 Furthermore, a prospective study demonstrated that cardiovascular morbidity was higher in nondippers than in dippers, 32 indicating that ADMA release by shear stress might contribute to the occurrence of cardiovascular events in human hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…2 We further showed that salt-sensitive hypertension manifests an absent or decreased nocturnal reduction in blood pressure, 30 and nondippers, ie, patients with an absent or decreased nocturnal reduction in their blood pressure, tend to have more severe target-organ damage than do dippers, ie, those with a normal nocturnal decrease in blood pressure. 31 Furthermore, a prospective study demonstrated that cardiovascular morbidity was higher in nondippers than in dippers, 32 indicating that ADMA release by shear stress might contribute to the occurrence of cardiovascular events in human hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Salt sensitivity is an insidious “silent killer” since even in individuals with normal blood pressure it can lead to cardiovascular morbidity and mortality (3) and is associated with other diseases, e.g., asthma (4), gastric carcinoma (5), osteoporosis (6), and renal dysfunction (7), among others. High sodium intake can aggravate the morning surge of blood pressure even in salt-resistant subjects (8) that could be associated with increased cardiovascular risk, in some studies (9). Although some studies suggest that non-dipping hypertension associated with low morning surge could also be associated with decreased cardiovascular risk (10), high sodium intake is also associated with non-dipping hypertension which is associated with increased cardiovascular risk (11).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Recent reports suggest that morning surge is closely related to incidence of cardiovascular and cerebrovascular diseases. 25,26 Blood pressure and salt intake differ in individuals and on different days. Thus, it would be useful to measure morning blood pressure and salt intake with the new salt monitor and to examine the relationship between blood pressure and salt intake for a relatively long period.…”
Section: Introductionmentioning
confidence: 99%